Discursive space in the discourse of a woman school leader - Thawley, Sarah (Rhodes University, Faculty of Education, Department of Education, 2006)
Women in leadership has become an increasingly popular area of research within the field of Educational Leadership and Management. As women hold more leadership roles and responsibilities in education it is increasingly important this subject is researched to enrich our understanding and knowledge of an area in which there have been silences. This research is a case study of a woman school leader in Namibia. The purpose was to explore the language she used and the impact of the discourses emerging from the text. The discourses are explained, described and interpreted through a critical discourse analysis to examine the discursive space and its relationship to the organisation. A feminist post-structural framework provided the basis for the critical orientation of this research. The findings of this study indicate that the leader occupied a discursive space of multiple positions that perpetuated and reproduced the school's organizational structure and culture. The significance of this study lies in the possibilities for future research. The use of a poststructural framework to critically analyze discourses, combined with the use of leadership and management theory provided a means by which to explore and understand the multiple positions a woman leader takes up. By analyzing the discursive space in a discourse researchers are able to explore new ways of examining women and leadership in education.
Keywords: Educational leadership -- Namibia; Women school administrators -- Namibia; School management and organization -- Namibia; Discourse analysis